Analisis Makna Leksikal Percakapan Dalam Program Acara "Mata Najwa" Dan Implementasinya Dalam Pembelajaran Bahasa Indonesia Di Sma - Purnamasari, Lisa; , Drs. Agus Budi Wahyudi, M.Hum (2016)
On every conversation it consist of leksical meaning as the way of diction. The object of this study was to know the form of lexical meaning on Mata Najwa conversation at Metro TV April 2016 edition and to know the implementation of the used of lexical meaning on Indonesian language teaching learning at senior highschool. Data source of this study was the uterance said by Najwa Shihab and other source in Mata Najwa Metro TV program. Technique of collecting data the researcher used noting technique. The theory used by the researcher was Chaer theory. The type of this research was qualitaitve descriptive. The researcher analyzed this research by collecting the data, data reduction, presenting the data, and conclude and verification. This research shows that the form of lexical meaning in Mata Najwa Metro TV program April 2016 edition consists of denotative, kognitive, ideational, konotative, reflective and idiomatic. It was called as denotative, refrencial, conceptual or ideational because the meaning of this appears because of the impact of feeling association of its users to the lexem that prononounce and listened. In denotative, kognitive, ideational, konotative, reflective and idiomatic it shows the symbols that uttered by the source with certain purpose. Considered that Mata Najwa is one of controversion politic debat program, so the source always tried to shows their domination and intelegence as part of government.